Changes in Health and Antiretroviral Adherence Among HIV-Infected Adults in Kenya: Qualitative Longitudinal Findings from a Livelihood Intervention - Weiser, Sheri D. (AIDS Behav, 2017)
This longitudinal qualitative study sought to understand how and why a livelihood intervention affected the health and health behaviors of HIV-infected Kenyan adults. The intervention included a microfinance loan, agricultural and financial training, and a human-powered water pump. In-depth interviews were conducted at two time points with intervention and control participants and program staff. We double coded interviews (n = 117) and used thematic content analysis of transcripts following an integrative inductive–deductive approach. Intervention participants described improvements in HIV health, including increased CD4 counts and energy, improved viral suppression, and fewer HIV-related symptoms. Better health was linked to improved clinic attendance and ART adherence through several mechanisms: (1) reductions in food insecurity and abject hunger; (2) improved financial stability; (3) improved productivity which enhanced social support; (4) better control over work situations; and, (5) renewed desire to prioritize their own health. Livelihood interventions may improve health by influencing upstream determinants of health behavior including food security and poverty.